223 Are we raising "normal" cows? Effects of early life diet, feeding plan, and housing on the natural behavior of dairy cattle. (7th December 2018) - Costa, J
Abstract: Young calves naturally form social relationships with the dam and other conspecifics in the first weeks of life, and they rely upon these relationships to learn about their environment, and to facilitate behavioral and cognitive development. This interaction with the environment, different feed types and other con-specifics are fundamental to the proper development of these animals. However, the industry standard management removes and isolates the calf from its dam and other calves, provides a restricted milk allowance, and houses these animals in a barren environment. Research shows there are significant negative effects of these practices on social and cognitive development as well as on growth of the neonate during the milk-feeding period. Unfortunately, there is limited work on the long-term effects possibly due to challenges associated with maintaining adequate controls and time constraints; there is some evidence that early-life impairments persist to adulthood. For instance, dam-reared calves showed greater locomotion in an isolation test, improved maternal behaviour, and transitioned into the lactating herd easier, years later. Furthermore, dam-reared calves were more accepting (less neophobic) of novel feed types, and developed exploratory feeding behavior quicker than isolated calves. These studies suggest rearing calves in a complex social environment may enhance social skills and adaptability later in life. This growing scientific evidence suggests current management practices may be raising animals that are far from 'normal'. There is a need to incorporate our knowledge of the natural, social, and nutritional environments of young cattle to revise current practices of intensive production systems and target optimal animal welfare and production. We offer examples of how this can be achieved by implementing social models, complex environments, and how to present novelty to cattle.